2013
DOI: 10.1152/ajpendo.00373.2012
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acids alter neurobehavioral function in rats

Abstract: Newgard CB. Branched-chain amino acids alter neurobehavioral function in rats. Am J Physiol Endocrinol Metab 304: E405-E413, 2013. First published December 18, 2012 doi:10.1152/ajpendo.00373.2012.-Recently, we have described a strong association of branched-chain amino acids (BCAA) and aromatic amino acids (AAA) with obesity and insulin resistance. In the current study, we have investigated the potential impact of BCAA on behavioral functions. We demonstrate that supplementation of either a high-sucrose or a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 76 publications
3
43
0
Order By: Relevance
“…Thus, this suggests that TRP and KYNA may produce an amplified effect in central fatigue. The role of KYNA in fatigue that we report is supported by the recent findings39 that administration of a branched-chain amino acid that lowers exercise-induced fatigue also reduces the higher levels of KYNA in the brain. Moreover, it has been reported that exogenous KYNA increases fatigability and the administration of KYNA into the hippocampus decreases neurocognition 12.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, this suggests that TRP and KYNA may produce an amplified effect in central fatigue. The role of KYNA in fatigue that we report is supported by the recent findings39 that administration of a branched-chain amino acid that lowers exercise-induced fatigue also reduces the higher levels of KYNA in the brain. Moreover, it has been reported that exogenous KYNA increases fatigability and the administration of KYNA into the hippocampus decreases neurocognition 12.…”
Section: Discussionsupporting
confidence: 88%
“…During this period, HFD and BCAA groups consumed more kilocalories than the control group [significant main effects of HFD, F (1,68)  = 22.75, p  <   .001; and BCAA, F (1,68)  = 15.63, p  <   .001; Figure 2b], likely due to the greater palatability and/or energy density of these diets (Coppola et al., 2013). However, HFD/BCAA animals gained significantly more weight per kilocalorie consumed than did all other diet groups over the 6 weeks on diet [significant HFD X BCAA interaction, F (1,185)  = 16.84, p  <   .001; post hoc, p  <   .05; Figure 2c], suggesting an effect of diet on metabolic regulation, or digestion efficiency/absorption.…”
Section: Resultsmentioning
confidence: 99%
“…no. D06050807; n  =   60] (Coppola et al., 2013). The HFD and HFD/BCAA diets provided 4.7 kcal/g; the LFD provided 3.84 kcal/g; and the LFD/BCAA provided 3.85 kcal/g.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, Kaddurah-Daouk and co-workers identified that lower plasma levels of branched chain amino acids (BCAAs) correlate with positive treatment outcomes. These results on BCAAs in CNS disorders are very timely as Newgard and co-workers determined that supplementation in BCAA was associated with anxiety-like phenotypes in the mouse (Coppola et al 2013 were associated with a particular form of heritable autism with epilepsy (Novarino et al 2012). These three studies suggest that BCAAs (and potentially other metabolites) play a prominent role in CNS disorders and that metabolic profiles can predict treatment outcomes in the clinical setting.…”
Section: Future Challenges and Unddressed Questionsmentioning
confidence: 93%